2022
DOI: 10.3389/fphar.2022.890330
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fresh Gastrodia elata Blume on the cognitive deficits induced by chronic restraint stress

Abstract: Chronic restraint stress (CRS) is a classic animal model of stress that can lead to various physiological and psychological dysfunctions, including systemic neuroinflammation and memory deficits. Fresh Gastrodia elata Blume (FG), the unprocessed raw tuber of Gastrodia elata Blume, has been reported to alleviate the symptoms of headache, convulsions, and neurodegenerative diseases, while the protective effects of FG on CRS-induced cognitive deficits remain unclear. This work aimed to evaluate the effects of FG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Animals were randomly divided into five groups, namely, the control group, model group, positive drug group (Donepezil, 1.6 mg/kg), FG low-dose group (0.5 g/kg), and high-dose group (1.0 g/kg). The dose of Donepezil was determined by previous literature ( Yang et al, 2020 ), and the doses of FG were according to our preliminary experiments and literature reports ( Huang et al, 2021 ; Huang et al, 2022 ). Oral administration was at a volume of 20 mL/kg and started at the same time as the modeling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were randomly divided into five groups, namely, the control group, model group, positive drug group (Donepezil, 1.6 mg/kg), FG low-dose group (0.5 g/kg), and high-dose group (1.0 g/kg). The dose of Donepezil was determined by previous literature ( Yang et al, 2020 ), and the doses of FG were according to our preliminary experiments and literature reports ( Huang et al, 2021 ; Huang et al, 2022 ). Oral administration was at a volume of 20 mL/kg and started at the same time as the modeling.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, water extract of Fresh Gastrodia elata Blume (FG) was used, which is a new and original form that maintains its original nutritional value compared with the processed form and is commonly used in herbal cuisine ( Huang et al, 2021 ). Moreover, our previous research has proved that FG has great benefits for improving cognitive impairment caused by circadian rhythm disorder and chronic restraint stress in mice, both of which are problems faced by astronauts during spaceflight ( Huang et al, 2021 ; Huang et al, 2022 ). The present study was designed to investigate the effect of FG on cognitive impairment induced by a simulated weightlessness model to explore the potential application value of FG in aerospace medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, KEGG enrichment analysis from 82 down-regulated genes showed that these genes were involved in signaling pathways, including PI3K/Akt (scatter plot; Figure 3D). Similarly, the CRS-treated ICR mice were subjected to cognitive deficits with the decreased AKT/mTOR in hipppocampus (Huang et al, 2022). The analysis found that the PI3K/Akt and MAPK signaling pathway were significantly changed in CRS-treated mice.…”
Section: The Pi3k/akt and Mapk Signaling Pathway Were Significantly C...mentioning
confidence: 96%
“…The step-down test was performed to evaluate the cognitive and memory functions of the rats [21,22], and was divided into a learning phase and a memory phase. The step-down test was performed with a Step-down Recorder (DB097, ShuduoBao, Beijing, China).…”
Section: Step-down Testmentioning
confidence: 99%